Proposed guidelines for the creation of an updated records management program for Valenzuela Medical Center (VMC) - Ladrera, Maribel R. (2014)
The focus of this study is the management of medical records from creation to disposition. Having a Records Management Program is a valuable tool that will serve as a guide for the effective and efficient management of medical records. The Valenzuela Medical Center (VMC) is the main subject of this study. Leading hospitals in the Philippines were also included such as the Medical City (TMC) and St. Luke's Medical Center (SLM|C) as benchmark hospitals.